Ets‐1 controls breast cancer cell balance between invasion and growth. Issue 10 (5th May 2014) - Furlan, Alessandro; Vercamer, Chantal; Bouali, Fatima; Damour, Isabelle; Chotteau‐Lelievre, Anne; Wernert, Nicolas; Desbiens, Xavier; Pourtier, Albin
<x xml:space="preserve">Abstract</x> Ets‐1 overexpression in human breast cancers is associated with invasiveness and poor prognosis. By overexpressing Ets‐1 or a dominant negative mutant in MMT breast cancer cells, we previously highlighted the key role of Ets‐1 in coordinating multiple invasive features of these cells. Interestingly, we also noticed that Ets‐1 decreased the density of breast cancer cells cultured in three‐dimensional extracellular matrix gels. The 3D context was instrumental to this phenomenon, as such downregulation was not observed in cells grown on two‐dimensional plastic or matrix‐coated dishes. Ets‐1 overexpression was deleterious to anchorage‐independent growth of MMT cells in soft agar, a standard model for in vitro tumorigenicity. The relevance of this mechanism was confirmed in vivo, during primary tumor growth and in a metastatic assay of lung colonization. In these models, Ets‐1 was associated with epithelial‐to‐mesenchymal transition features and modulated the ratio of Ki67‐positive cells, while hardly affecting in vivo apoptotic cell death. Finally, siRNA‐mediated knockdown of Ets‐1 in human breast cancer cell lines also decreased colony growth, both in anchorage‐independent assays and 3D extracellular matrix cultures. These in vitro and in vivo observations shed light on an unsuspected facet of Ets‐1 in breast tumorigenesis. They show that while promoting malignancy through the acquisition of invasive features, Ets‐1 also attenuates breast tumor cell growth and could therefore repress the growth of primary tumors and metastases. This work also demonstrates that 3D models may reveal mechanisms of tumor biology that are cryptic in standard 2D models.